EFFECTIVENESS OF HEALTH EDUCATION WITH FLIPCHART MEDIA ON IMPROVING QUALITY OF LIFE AND DIET COMPLIANCE IN HYPERTENSION PATIENTS - Yobel, Sosilo; Kristiani, Rina Budi (Lux Mensana: Journal of Scientific Health, 2023)
Introduction. The problem is, there are still many hypertension sufferers who don't take care of their diet that which can affect the condition and lead to complications that impact on quality of life. The purpose of this study was to determine the effectiveness of health education using flipchart media to improve quality of life and dietary compliance in hypertensive patients. Method. This research is a pre-experimental study with the "One Group Pretest-Posttest design without control" approach. The sample is 18 elderly who suffer from hypertension. Analysis to find out the difference in average hypertension sufferers before and after health education was carried out using the Wilcoxon signed ranks test. Results & Analysis. The Wilcoxon test showed a P value = 0.000 (P<0.05), there was an effect of health education on quality of life and dietary adherence. Discussion. Hypertensive patients can make strides in their quality of life and dietary commitment after being given well-being instruction utilizing flipchart media, usually upheld by the capacity to tune in mindfully and communicate well to encourage decision-making approximately utilizing methodologies to make strides in the quality of life.